Book Review, Immigrant Japan: Mobility and Belonging in an Ethno-nationalist Society, by Gracia Liu-Farrer - Firman Budianto (Jurnal Kajian Wilayah, 2020)
Gracia Liu-Farrer’s Immigrant Japan: Mobility and Belonging in an Ethno-Nationalist Society is an intellectually stimulating invitation to rethink the traditional definition of immigrant country in an age of global mobility. The book provides the readers with rich narratives to understand how the immigration takes place in an immigrant society that emerged out of an ethno-nationalist one. Through the analysis of narratives of belonging and mobility, Liu-Farrer has shown how international migration occurs in non-traditional receiving countries, challenged the traditional definition of an immigrant country, and offered a promise of future Japan as an immigrant country. The book presents an essential addition to the literature on Japanese studies, area studies, and international migration and mobilities in Japan and beyond. It shows that micro-level individual narratives on mobility could pave the way to understanding transnationalism and connectivity at a larger scale as well as socio-cultural change taking place in a particular area. The book, finally, contributes to broadening the concept of an immigrant country, especially in the age of global mobility.